Human behavior in organizations - Vandeveer, Rodney C.; Menefee, Michael L. (Upper Saddle River, New Jersey : Pearson Prentice Hall, 2020)
Java Programming, From The Ground Up, with its flexible organization, teaches Java in a way that is refreshing, fun, interesting and still has all the appropriate programming pieces for students to learn. The motivation behind this writing is to bring a logical, readable, entertaining approach to keep your students involved. Each chapter has a Bigger Picture section at the end of the chapter to provide a variety of interesting related topics in computer science. The writing style is conversational and not overly technical so it addresses programming concepts appropriately. Because of the flexible organization of the text, it can be used for a one or two semester introductory Java programming class, as well as using Java as a second language.
1. What is organizational behavior? -- 2. Personality, ability, and learning -- 3. Perception -- 4. Values and attitudes -- 5. Motivation -- 6. Stress -- 7. Turning people into team players -- 8. Group behavior -- 9. Leadership -- 10. Decision making -- 11. Communication -- 12. Conflict -- 13. Negotiation -- 14. Typical structures -- 15. What do people in different jobs do? -- 16. Human resources I : the hiring process -- 17. Human resources II : company policies -- 18. Organizational culture -- 19. Motivation in organizations -- 20. Organizational change -- 21. Power and politics -- 22. Effort and ethics -- 23. Succeeding in an organization.
Third Custom Edition for Purdue University.
Includes index.
Keywords: ORGANIZATIONAL BEHAVIOR